A Potential Method for Enhanced Performance of Nimodipine by Spanlastic Nanovesicle with Tween 40 as Edge Activator - Hussein K. Alkufi; kassab, hanan (Iraqi Journal of Pharmaceutical Sciences, 2025)
This investigation aimed to investigate the potential of utilizing nanospanlastics to improve the bioavailability of nimodipine (NMD). To treat subarachnoid hemorrhage-induced vasospasm, physicians prescribe NMD, an FDA-approved drug. Intravenous (IV) administration is the most common way to provide NM, and it can have several unfavorable effects, including injection site irritation, bradycardia, hypotension, and arrhythmias. Made up of surfactants and edge activators (EAs), nanospanlastics are malleable nanovesicles. EAs improve the deformability of spanlastics by acting as a stabilizing force on their vesicular membranes. To make NMD-loaded spanlastics, ethanol was injected according to a 23 factorial design. This was done to see how different factors affected particle size, PDI, and entrapment efficiency (EE%). Stability investigations, FESEM, FTIR, DSC, and in vitro characterization were performed on the optimized formula. The optimized formula (F19) demonstrated a notable improvement in EE% and stability, as well as longer drug release. Nanospanlastics not only made NMD much more soluble and bioavailable, but it also made it a more appealing nanoplatform for hydrophobic drug delivery.